Effect of Azolla and Beef Bone Meal Addition on the Nutrient Content of LOF Based on Beef Cattle Manure and Laying Hens Excreta - Safitry, Rania Zabina; Ridwan, Roni; Harlia, Ellin (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
In Liquid Organic Fertilizer (LOF), the problem that is often found is that the nutrients contained do not reach quality standards. Azolla and beef bone meal are known to contain macronutrients needed by plants, in addition to maximizing the existing content, functional bacteria are also added. This study aims to analyze the effect of the addition of azolla and beef bone meal on macro nutrient content, C-organic, coliform, and viability. The research method uses a completely randomized design (CRD) with 6 treatments and 3 replicates, namely (P1) 25% Azolla + 15% beef bone meal, (P2) 25% Azolla + 20% beef bone meal, (P3) 25% Azolla + 25% beef bone meal, (P4) 25% azolla + 15% beef bone meal + 10% functional bacteria, (P5) 25% azolla + 20% beef bone meal + 10% functional bacteria, (P6) 25% azolla + 25% beef bone meal + 10% functional bacteria. The research data were analyzed statistically using variance analysis and Duncan's multiple range test with the IBM SPSS Statistics 25 program. The results showed that the addition of 25% azolla + 25% beef bone meal (P3) had a significant effect (P≤0.05) on increasing macro nutrient content and functional bacteria viabilty, C-organic, coliform.